2020
DOI: 10.1016/j.envpol.2019.113859
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the impacts of e-waste towards marine bivalves: The case of the rare earth element Dysprosium

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…These results suggest that, despite efforts to avoid Y accumulation by lowering or maintaining aerobic respiration, the presence of Y resulted in greater energetic usage, probably associated with demands in antioxidant and detoxification defenses. Likewise, a decline of glycogen was formerly seen in mussels, M. galloprovincialis , exposed to other REEs such as Nd and dysprosium (Dy), which was also indicated to provide protection (Freitas, Cardoso, et al, 2020 ; Freitas, Costa, et al, 2020 ). In the particular case of intertidal mussels, the decrease in GLY was also associated with its use in anaerobiosis (De Zwaan, 1983 ; Hochachka & Mustafa, 1972 ).…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest that, despite efforts to avoid Y accumulation by lowering or maintaining aerobic respiration, the presence of Y resulted in greater energetic usage, probably associated with demands in antioxidant and detoxification defenses. Likewise, a decline of glycogen was formerly seen in mussels, M. galloprovincialis , exposed to other REEs such as Nd and dysprosium (Dy), which was also indicated to provide protection (Freitas, Cardoso, et al, 2020 ; Freitas, Costa, et al, 2020 ). In the particular case of intertidal mussels, the decrease in GLY was also associated with its use in anaerobiosis (De Zwaan, 1983 ; Hochachka & Mustafa, 1972 ).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, there is evidence that only 20% (almost 8.9 Mt) of the collected e-wastes are properly recycled, with approximately 40 Mts to end up in dumpsites and landfills, where they are either buried or burnt [ 9 , 10 ]. In all cases, their entrance into the environment is considered inevitable through leaching and transport with water, air and soil, thus contaminating both surface and groundwater bodies, as well as coastal basins [ 8 , 11 ]. For instance, several monitoring studies performed near e-waste treatment and workshop sites in developing countries revealed air, soil, and surface waters contamination with e-waste leaching components, mainly heavy metals ([ 12 , 13 , 14 , 15 , 16 , 17 ], as well as other toxic substances such as dioxins, polyaromatic hydrocarbons (PAHs), polychlorinated biphenyl (PCBs), brominated flame retardants (BFRs), polybrominated diphenyl ethers (PBDEs), and polychlorinated dibenzo-p-dioxin furans (PCDD/Fs) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCMBs account for almost 6–9% of the total weight of PCs [ 20 ], and possess high concentrations of heavy metals, like Ag, As, Au, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb, Se, U, and Zn, as well as uranium, bromine, Rare Earth Elements (REEs). and Platinum Group Metals (PGMs, like Ir, Pd, Pt and Rh), whose leaching could be harmful to both aquatic biota and human health [ 11 , 21 , 22 , 23 ]. Moreover, it has been recently reported that inappropriate handling or primitive recycling processes of e-wastes could lead to the release of dioxins, polybrominated diphenyl ethers (PBDEs), as well as radioactive isotopes [ 10 , 24 ], thus being responsible for air, soil, and water resources contamination [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason why the causes of accidents due to environmental risks have been largely disregarded until last years is that intense increase in demands on a global scale. In fact, with continued industrial applications of REEs due to increased mineral demand and use, as well as imprecise discharge of contaminats containing these materials into the receiving bodies, concentrations of REEs can reach extreme levels in receiving environments (Freitas et al, 2020), For these reasons, problems of exceeding recorded levels in natural water, which are generally in the range of a few ng/L to a few μg/L, can pose a threat. (Verplanck et al, 2001).…”
Section: Introductionmentioning
confidence: 99%